FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN PENYAKIT DEMAM BERDARAH DENGUE DI KABUPATEN KAMPAR - Siti Nurjannah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
Indonesia has a high risk of contracting Dengue Hemorrhagic Fever due to dengue virus and its mosquito transmission, Aedes Aegypty, which is widespread throughout rural and urban areas, both at home and in public places, except for areas with elevations of more than 1,000 meters from sea level. Data in Kampar district the number of DHF cases as many as 307 (IR = 41.7 / 100,000 Population) is still far above the national target IR =